2016
DOI: 10.1017/s0025315416001715
|View full text |Cite
|
Sign up to set email alerts
|

Distribution pattern, density and growth of the stout razor clam Tagelus plebeius in a South-west Atlantic estuarine system

Abstract: The population biology of the stout razor clam Tagelus plebeius is poorly understood, despite the species' current wide distribution, and the potential use of its Holocene shell deposits to infer past environmental and ecological conditions. This study investigates distribution and growth pattern of T. plebeius in the south-western Atlantic Mar Chiquita Coastal lagoon (37°32′S 57°19′W), Argentina. The population includes the oldest individuals (up to 27 years) reported so far with shell length up to 77.9 mm. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 51 publications
(87 reference statements)
0
5
1
Order By: Relevance
“…Thus, differences in growth parameters are not related to temperature. A previous study in MC showed somewhat different values for Tagelus plebeius k and L∞ (k = 0.181, L∞ = 67.60, Lomovasky et al, 2016) when compared with the present study. Nevertheless, these differences may be due to the use of clams pooled from different locations along the salinity gradient and with ages ranging from 0 to 27 years old, while the range of ages in this study was from 3 to 17.…”
Section: Discussioncontrasting
confidence: 84%
See 3 more Smart Citations
“…Thus, differences in growth parameters are not related to temperature. A previous study in MC showed somewhat different values for Tagelus plebeius k and L∞ (k = 0.181, L∞ = 67.60, Lomovasky et al, 2016) when compared with the present study. Nevertheless, these differences may be due to the use of clams pooled from different locations along the salinity gradient and with ages ranging from 0 to 27 years old, while the range of ages in this study was from 3 to 17.…”
Section: Discussioncontrasting
confidence: 84%
“…Sampling of abiotic variables were carried out in the medium intertidal level (following Lomovasky et al, 2016), where along the semidiurnal tide cycle the water covers when flooding and uncover when ebbing in every tidal cycle. To describe salinity and to verify the patterns reported in the literature (Piccolo and Perillo, 1997;Reta et al, 2001;Isacch et al, 2006), water samples were taken monthly or bimonthly depending on logistical constrains and salinity was measured with a handheld refractometer.…”
Section: Physical Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results suggest that shell growth of B. rodriguezii exhibited a considerable seasonality, probably due to the increment of food availability and water temperature. Other molluscs from the region like Zidona dufresnei (Donovan, 1823) (Giménez et al 2004), the wedge clam Donax hanleyanus Philippi, 1847 (Herrmann et al 2009), and the razor clam Tagelus plebeius (Lightfoot, 1786) (Lomovasky et al 2018), exhibit the same growth pattern, showing a greater increase in shell length when water temperature was higher.…”
Section: Discussionmentioning
confidence: 99%